Archaeal and bacterial H-GDGTs are abundant in peat and their relative abundance is positively correlated with temperature. (15th April 2018) - Naafs, B.D.A.; McCormick, D.; Inglis, G.N.; Pancost, R.D.; ,
Abstract: Glycerol monoalkyl glycerol tetraether lipids (GMGTs; also called 'H-GDGTs') differ from the more commonly studied glycerol dialkyl glycerol tetraether (GDGTs) in that they have an additional covalent bond that links the two alkyl chains. Six different archaeal isoprenoidal H-GDGTs (H- iso GDGTs) and one branched H-GDGT (H- br GDGT), presumably produced by bacteria, have previously been found. However, the function of H-GDGTs in both domains of life is unknown. It is thought that the formation of this additional covalent bond results in enhanced membrane stability, accounting for the high abundance of H-GDGTs in extreme environments such as geothermal settings, but so far there has been little evidence to support this hypothesis. Here we report the distribution of H-GDGTs in a global peat database ( n = 471) with a broad range in mean annual air temperature (MAAT) and pH. This is the first finding of H-GDGTs in soils (specifically, peat), highlighting that H-GDGTs are widespread in mesophilic settings. In addition, we report the presence of two new H- br GDGTs with one (H-1034) and two (H-1048) additional methyl groups, respectively. Our results suggest that the relative abundance of both bacterial and archaeal H-GDGTs compared to regular GDGTs is related to temperature with the highest relative abundance of H-GDGTs in tropical peats. Although other factors besides temperature likely also play a role, these results do support the hypothesis that H-GDGTs are an adaptation to temperature to maintain membrane stability. The observation that both bacterial and archaeal membrane lipids respond to temperature indicates the same adaption across the lipid divide between these two domains of life, suggesting parallel or convergent evolution (potentially facilitated by lateral gene transfer).